Tumor (T) Staging and the Association with LMP1 Expression in NPC Patients (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: Nasopharyngeal carcinoma is disease derived from squamous cell epithelium. It is closely associate with EBV infection, which its latent infection express several genes, including latent membrane protein-1 (LMP1). LMP1 is associate with the growth of tumor by activating several signaling pathway and gene expression. Objective: This study was conducted to analyze the overexpression of LMP1 based on T stage. Methods: This was a cross-sectional design with statistical analysis. We used CT scan with contrast to evaluate the primary tumor size based on AJCC 2010. The overexpression of LMP1 was assessed by immunohistochemistry staining based on IRS. The study was conducted in Adam Malik General Hospital Medan, Indonesia. Fisher exact test was used to analyze the association of LMP1 overexpression and T stage. Results: Our study showed the overexpression of LMP1 was most common in stage T3 with 23 (37.1%) samples. Then followed by stage T4, T2, and T1 with 20 (32.3%), 16 (25.8%), and 3 (4.8%) samples respectively. There was not significant association of LMP1 overexpression with T stage (p > 0.05). Conclusion: The overexpression of LMP1 is found mostly in late T stage including T3 and T4. Different with our hypothesis, there was not association of T stage with LMP1 overexpression. We suggested the LMP1 was in indirect role in the growth of tumor as it not strong enough to affect the T stage. However, the highest expression in late stage supported for LMP1 used as prognostic biomarker and may be applicative in targeted therapy of nasopharyngeal carcinoma.